2006
DOI: 10.1007/s10584-005-9034-x
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Plant Species Changes on a Mire in the Italian Alps: Vegetation-Controlled or Climate-Driven Mechanisms?

Abstract: Abstract. Variation of plant species cover on a Sphagnum-dominated mire in the south-eastern Alps of Italy was assessed over a 10-year period in relation to depth to the water table, peat accumulation rate, and climate. Population dynamics of vascular species appeared to be primarily affected by the autogenic process of peat accumulation, which determined the lowering of water-table position at microhabitat scale. Increase of depth to the water table through peat accumulation resulted in increased cover of eri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…The observed loss of moisture in both plots dropping out of their bog alliances and plots remaining within it goes along with the observations of Bragazza (2006) on an southern Alpine bog and with the findings of Nordbakken (2001) and Gunnarsson et al (2002) in Swedish mires. Bragazza (2006) found autogenic reasons (mainly peat accumulation) for drying out, whereas Nordbakken (2001) and Gunnarsson et al (2002) name change in site factors to be responsible for it (reduced rainfall, altered waterflow from the surroundings).…”
Section: Vegetation Of Bogssupporting
confidence: 78%
See 1 more Smart Citation
“…The observed loss of moisture in both plots dropping out of their bog alliances and plots remaining within it goes along with the observations of Bragazza (2006) on an southern Alpine bog and with the findings of Nordbakken (2001) and Gunnarsson et al (2002) in Swedish mires. Bragazza (2006) found autogenic reasons (mainly peat accumulation) for drying out, whereas Nordbakken (2001) and Gunnarsson et al (2002) name change in site factors to be responsible for it (reduced rainfall, altered waterflow from the surroundings).…”
Section: Vegetation Of Bogssupporting
confidence: 78%
“…Bragazza (2006) found autogenic reasons (mainly peat accumulation) for drying out, whereas Nordbakken (2001) and Gunnarsson et al (2002) name change in site factors to be responsible for it (reduced rainfall, altered waterflow from the surroundings). Our observations support the findings of Nordbakken (2001) and Gunnarsson et al (2002) rather than those of Bragazza (2006): At the same time as the plots were drying out, we observed a loss of soil humus content and increased soil-nutrient contents, indicating that peat is rather decomposed than accumulated. Gunnarsson et al (2002) also found in Sweden increased soil nutrient availability and increasing populations of trees and dwarf shrubs.…”
Section: Vegetation Of Bogsmentioning
confidence: 99%
“…However, since peatland plant community compositions are known to be remarkably stable over time but experience changes in relative abundances (Rydin and Barber, 2001;Bragazza et al, 2006), we suggest that it was probably the vicinity to the reservoir that shaped the plant community composition at the sites over time, whereas the plant community actually drives C cycling.…”
Section: Long-term Insights Into Carbon Cycling At the Sitesmentioning
confidence: 89%
“…At deposition levels higher than 18 kg N ha −1 year −1 , Sphagnum spp. become saturated with N and excess N leaches deeper into the system, which facilitates growth of vascular plants, changes nitrogen cycling and decomposition rates, and may result in degradation of peatlands (Lamers et al 2000;Bragazza 2006;Wu and Blodau 2013;Novak et al 2015). Moreover, high N availability in the form of NH 4 + ultimately could become toxic to wetland plants, especially under P-limited conditions ).…”
Section: Introductionmentioning
confidence: 99%